Tar removal capacity of waste cooking oil absorption and waste char adsorption for rice husk gasification. Issue 4 (3rd July 2016) - Tarnpradab, Thanyawan; Unyaphan, Siriwat; Takahashi, Fumitake; Yoshikawa, Kunio
ABSTRACT: Tar removal by oil absorber and char adsorber known as the physical method is a promising technology for cleaning synthesis gas from biomass gasification offering high tar removal efficiency, low cost, uncomplicated operation and waste-free facility. However, it is essential to maintain tar removal efficiency to a satisfying level in order to prevent downstream application breakdown. Therefore, periodic changing of absorbent and adsorbent are highly required. In this paper, the tar removal capacity of waste cooking oil (WCO) and waste char (WC) is investigated to maximize waste utilization for gas cleaning pre-treatment systems. For WCO, the gravimetric tar removal reached the breakthrough point in the second hour and the capacity was 14.4 g-tar/L-WCO (80.6% and 94.6% of gravimetric tar and naphthalene removal performance on average). For WC, the breakthrough point was in the second hour for naphthalene removal and the capacity was 0.15 mg-naphthalene/g-waste char (76% of naphthalene removal performance) while it could also adsorb heavy tar with the capacity of 48.8 mg-tar/g-waste char. This increased the gravimetric tar removal efficiency by 3.1% when connecting the WC bed after the WCO scrubber.